2014
DOI: 10.1016/j.ejor.2013.12.020
|View full text |Cite
|
Sign up to set email alerts
|

Adjusting a railway timetable in case of partial or complete blockades

Abstract: Unexpected events, such as accidents or track damages, can have a significant impact on the railway system so that trains need to be canceled and delayed. In case of a disruption it is important that dispatchers quickly present a good solution in order to minimize the nuisance for the passengers. In this paper, we focus on adjusting the timetable of a passenger railway operator in case of major disruptions. Both a partial and a complete blockade of a railway line are considered. Given a disrupted infrastructur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
82
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(83 citation statements)
references
References 18 publications
1
82
0
Order By: Relevance
“…No literature references have been found that treat this subject. There is however some work done regarding the opposite problem of replanning a timetable or operative train plan due to track closures (complete or partial) or maintenance activities, for example in: Brucker et al (2005) (scheduling of single track traffic past a working site on a line section); Vansteenwegen et al (2015) (robust rescheduling due to planned track closures on large stations and junctions); and Louwerse and Huisman (2014) and Veelenturf et al (2015) (rescheduling of timetables, rolling stock and crew during major disruptions in operational dispatching). In all these cases the track closures / maintenance are given as fixed input.…”
Section: Reschedulingmentioning
confidence: 99%
“…No literature references have been found that treat this subject. There is however some work done regarding the opposite problem of replanning a timetable or operative train plan due to track closures (complete or partial) or maintenance activities, for example in: Brucker et al (2005) (scheduling of single track traffic past a working site on a line section); Vansteenwegen et al (2015) (robust rescheduling due to planned track closures on large stations and junctions); and Louwerse and Huisman (2014) and Veelenturf et al (2015) (rescheduling of timetables, rolling stock and crew during major disruptions in operational dispatching). In all these cases the track closures / maintenance are given as fixed input.…”
Section: Reschedulingmentioning
confidence: 99%
“…Given a disrupted infrastructure situation and a forecast of the characteristics of the disruption, the goal of the model was to design a disposition timetable, specifying which trains needed to still be in operation during the disruption and determining the timetable of these trains [19]. The definition and distinguishing characteristics between "disruption" and "disturbance" were demonstrated in a recent overview [20] in detail.…”
Section: Literature Reviewmentioning
confidence: 99%
“…An Integer Programming (IP) model for a partial blockage and a complete blockage which aimed at maximizing the service level to the train passengers was proposed by [5]. The model determines which trains need to be cancelled and it presents the disposition timetable for the neighbouring trains.…”
Section: Several Model Approaches For Rescheduling Have Been Proposedmentioning
confidence: 99%